Use the equation
For A. The problem would be set up like so
5 _ -1
--------
4 _ -2
Start by subtracting 5 minus -1 which is 6 because minus a negative becomes a positive then subtract 4 minus -2 which is 6, remember minus a negative becomes a positive, then divide 6/6 to get 1
For B.
-5 _ -0
----------
3 _ -1
Again subtract -5 by -0 which no matter what will be -5. Then make -1 positive because it's a subtracted negative so it becomes 3+1 which gives you 4. Your answer is -5/4
If you need help with the rest message me good luck
Answer:
35 ft
Step-by-step explanation:
See attached file for detailed solution of the given.
| x + 4 | = 5
x + 4 = 5 x + 4 = -5
x = 5 - 4 x = -5 - 4
x = 1 x = -9
solution : x = 1 and x = -9
Exact Form:
x
=
2
√
2
,
−
2
√
2
,
−
1
,
1
x
=
2
2
,
-
2
2
,
-
1
,
1
Decimal Form:
x
=
2.82842712
…
,
−
2.82842712
…
,
−
1
,
1